Revealing academic web interlinking motives through webometrics and statistical techniques: Nigerian university websites as a case study. (2016) - Nwohiri, Anthony M.; Pechnikov, Andrey A.
The websites of the universities of Africa's most populous country Nigeria were examined. The goal was to unearth the reasons why external hyperlinks are placed on these sites and identify any peculiarities by geographical location. Academic website interlinking motivations were formulated. Over 6, 000 hyperlinks placed on the websites of 86 Nigerian universities were categorised under these interlinking motivations. Categorising the motivations by examining the source and target pages of each hyperlink was an arduous task. Statistical analysis offered a clearer picture of the interlinking motives. A chi-squared test revealed distinctive features, which are characteristic of specific geographical regions of Nigeria. The study serves as a route to further research on feasibility of findings in other developing countries. Results obtained could be of great importance for academic webpage developers and authors. The results could modify their work towards improving the use of hyperlinks as a major communication tool on the web.